Plant Hormesis Management with Biostimulants of Biotic Origin in Agriculture - Vargas-Hernandez, Marcela; Macias-Bobadilla, Israel; Guevara-Gonzalez, Ramon G.; Romero-Gomez, Sergio de J.; Rico-Garcia, Enrique; Ocampo-Velazquez, Rosalia V.; Alvarez-Arquieta, Luz de L.; Torres-Pacheco, Irineo (Frontiers in Plant Science, 2017)
Over time plants developed complex mechanisms in order to adapt themselves to the environment. Plant innate immunity is one of the most important mechanisms for the environmental adaptation. A myriad of secondary metabolites with nutraceutical features are produced by the plant immune system in order to get adaptation to new environments that provoke stress (stressors). Hormesis is a phenomenon by which a stressor (i.e toxins, herbicides, etc) stimulates the cellular stress response, including secondary metabolites production, in order to help organisms to establish adaptive responses. Hormetins of biotic and abiotic origin (ie. biostimulants), in certain doses might enhance plant performance, however in excessive doses they are commonly deleterious. Biostimulants of biotic origin are called “elicitors” that have widely been studied as inducers of plant tolerance to biotic and abiotic stresses. The plant response toward elicitors is reminiscent of hormetic responses toward toxins in several organisms. Thus, controlled management of hormetic responses in plants using biostimulants of biotic origin (elicitors) is expected to be an important tool to increase nutraceutical quality of plant food and trying to minimize negative effects on yields. The aim of this review is to analyze the potential for agriculture that the use of biostimulants of biotic origin could have in the management of the plant hormesis. The use of new biostimulants in crop production is also discussed.